COVID 19 LOCKDOWN AND MEDIA: A STUDY ON SELECTED EDITORIALS - PRAVEEN KUMAR , DR. SRIDHAR KRISHNASWAMI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Editorials’ aptitude lies in the progressions they make to social orders. These communicated opinions tackle current issues and attempt to discover proof to demonstrate speculations and answer genuine and complex inquiries. This paper tries to understand the response of media to the nationwide lockdown that was announced to combat the ongoing pandemic. It uses Critical Discourse Analysis to identify the markers placed in the selected editorials to draw conclusion on their reaction.